A Genomic Study of DNA Alteration Events Caused by Ionizing Radiation in Human Embryonic Stem Cells via Next-Generation Sequencing. (22nd November 2015) - Nguyen, Van; Panyutin, Irina V.; Panyutin, Igor G.; Neumann, Ronald D.
Abstract : Ionizing radiation (IR) is a known mutagen that is widely employed for medical diagnostic and therapeutic purposes. To study the extent of genetic variations in DNA caused by IR, we used IR-sensitive human embryonic stem cells (hESCs). Four hESC cell lines, H1, H7, H9, and H14, were subjected to IR at 0.2 or 1 Gy dose and then maintained in culture for four days before being harvested for DNA isolation. Irradiation with 1 Gy dose resulted in significant cell death, ranging from 60% to 90% reduction in cell population. Since IR is often implicated as a risk for inducing cancer, a primer pool targeting genomic "hotspot" regions that are frequently mutated in human cancer genes was used to generate libraries from irradiated and control samples. Using a semiconductor-based next-generation sequencing approach, we were able to consistently sequence these samples with deep coverage for reliable data analysis. A possible rare nucleotide variant was identified in the KIT gene (chr4:55593481) exclusively in H1 hESCs irradiated with 1 Gy dose. More extensive further studies are warranted to assess the extent and distribution of genetic changes in hESCs after IR exposure.